PENGARUH KOMPETENSI SOSIAL GURU TERHADAP PENGUATAN JIWA MODERASI BERAGAMA PESERTA DIDIK DI MADRASAH ALIYAH MUHAMMADIYAH METRO LAMPUNG - Aldi Kurniawan; Iswati; Heri Cahyono; Bayu Ardiwansyah (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
This study aims to analyze the influence of teachers’ social competence on strengthening students’ religious moderation at Madrasah Aliyah Muhammadiyah Metro, Lampung. The background of this research is the crucial role of teachers in instilling values of tolerance, mutual respect, and the ability to live harmoniously in a plural society, amidst challenges such as fanaticism, narrow religious understanding, and difficulties in accepting differences. This research employed a quantitative approach with a survey method involving 70 students as the population. Data were collected through questionnaires tested for validity and reliability, supported by documentation and interviews. The data were analyzed using simple linear regression with the help of SPSS 22. The results show that teachers’ social competence falls into the good category, while students’ religious moderation is relatively high. The hypothesis test obtained a significance value of 0.000 < 0.05 with the regression equation Y = 13.781 + 0.681X, indicating that every increase in teachers’ social competence contributes to an increase in students’ religious moderation. Therefore, it can be concluded that teachers’ social competence has a positive and significant effect on strengthening students’ religious moderation in madrasah.